Comparison between cervical headgear and teuscher in the treatment of class II division I malocclusion - Jawad, Feras H. Abedal (My University, 2006)
Bu retrospektif çalışmanın amacı Class II divizyon 1 malokluzyonlu hastalarda servikal headgear ve Teuscher aygıtı ile yapılan farklı iki tip tedavi yaklaşımlarının sonunda oluşan iskeletsel, dişsel ve yumuşak doku değişikliklerini karşılaştırmaktır. Çalışma iki gruba ayrılmış olan 28 hastadan oluşmaktadır. İlk grup servikal headgear ile tedavi edilen 15 (6 erkek, 9 kız) bireyden, ikinci grup ise Teuscher aygıtı ile tedavi edilen 13 (8 erkek, 5 kız) bireyden oluşturulmuştur. Tüm bireyler iskeletsel olarak mandibular retrognatiye bağlı sınıf II malokluzyonlu ve artmış overjeti olan bireylerdir. Tedavinin başında ve sınıf I ilişki elde edildiğinde lateral sefalometrik radyografiler alınmıştır. Ortalama tedavi süreleri servikal headgear grubu için 2,18 yıl, Teuscher aygıtı grubu için 2,73 yıldır. Sonuçlar, her iki aygıtın da sagital iskeletsel ilişkiyi düzeltmesi açısından etkili bulunmuştur ve bu etki önemli miktarda üst çene büyümesinin engellenmesine eşlik eden minimal alt çene büyümesi ile gerçekleşmiştir. Servikal headgear grubunda alt çene düzlem açısı artmış, Teuscher grubunda sabit kalmıştır. Servikal headgear grubunda palatal düzlem saat yönünde rotasyon yaparken Teuscher grubunda okluzal düzlem saat yönünün tersine rotasyon yaptığı bulunmuştur. Gruplar arasında sadece Teuscher grubunda azalmış olan Gonial açı önemli farklılık göstermiştir. Teuscher aygıtı, alt keserlerin labial devrilmesini kontrol etmede etkili olmuştur. Her iki aparey de yumuşak doku profilinin düzelmesinde etkili olmuşken Teuscher grubunda daha belirgindir.

Comparison Between Cervical Headgear And Teuscher In The Treatment Of Class II Division I Malocclusion The aim of this retrospective study was to compare and dissect skeletal, dental, and soft tissue changes achieved following the use of cervical headgear and Teuscher in the treatment of Class II division 1 patients. This study comprised of 28 patients who were divided into two groups. The first group comprised of 15 patients (6 males, 9 females) treated with cervical headgear, and the second group included 13 patients (8 males, 5 females) treated with Teuscher. All subjects were skeletally Class II with mandibular retrusion and increased overjet. Lateral cephalometric radiographs taken at the start of the treatment, and following achievement of Class I molar relationship were used in the study. The average duration of treatment was 2,18 years for cervical headgear group, and 2,73 years for Teuscher group. The results revealed that both appliances were effective in correcting sagittal skeletal relationship, and the major effect was due to maxillary restraining with minimal mandibular growth. Mandibular plane angle was increased in the cervical headgear group, while remained stable in Teuscher group. Clockwise rotation of the palatal plane was found to occur in the cervical headgear group. Counterclockwise rotation of the occlusal plane was found in the Teuscher group. The only significant difference found between the groups is the Gonial angle which was decreased more in the Teuscher group. Teuscher was effective in controlling labial tipping of lower incisors. Both appliances improved the soft tissue facial profile, although it was more remarkable in Teuscher group.
Keywords: Diş ve Diş Hastalıkları_Tedavi; Ortodonti